Motivations and limitations on the use of Information Technology on statutory auditors’ work: an exploratory study - Pedrosa, I.; Costa, C.; Laureano, Raul M. S. (CISTI'2015 - 10th Iberian Conference on Information Systems and Technologies, 2015)
Nowadays is conceivable to say that is almost impossible to accomplish auditors’ tasks without using Information Technologies (IT). That discussion might be acceptable two decades ago but, now, is relevant to understand why are auditors using IT in their professional context and how could be possible, as stated in some authoritative bodies’ guidance, to improve the efficacy and efficiency of statutory auditors’ work. To accomplish previous objectives, an online survey was developed and applied to Portuguese Statutory Auditors. The motivations to use Computer-assisted Audit Tools (CAATs) will be discussed, either the constructs suggested by Unified Theory of Acceptance and Use of Technology (Performance Expectancy, Effort Expectancy, Social Influence and Facilitating Conditions) or new motivations’ dimensions suggested from quantitative data analysis and open questions analyses?. This paper contributes in three relevant areas: first, by understanding the big picture on the motivations to use CAATs; second, to recognize the limitations that auditors still feel in using CAATs; and third, to propose strategies to overcome those difficulties.